AI FLUENCY FOR FUTURE HIGHER EDUCATION - Abd Latif Abdul Rahman (IC-BESTS: International Conference on Business, Economics, Technology, and Social Sciences, 2026)
Artificial intelligence (AI), digital technology, and agentic automation are transforming business, employment, and higher education. Based on Abdul Latif Abdul Rahman's IC-BESTS 2026 material and supported by recent Scopus-indexed literature, this conceptual article examines how higher education should prepare Generation Z for an AI-intensive labor market. The study uses a qualitative conceptual review by synthesizing presentation themes on Southeast Asian AI adoption, agentic AI, skill transformation, operational risks, and higher education strategy with academic studies on AI in education, AI literacy, ethics, assessment, and digital pedagogy. The findings indicate that higher education institutions must shift from producing graduates for routine clerical work to developing AI-fluent orchestrators who can prompt, critique, integrate, govern, and ethically collaborate with AI systems. The article proposes a four-pillar strategic blueprint: democratizing AI fluency across all faculties, redesigning learning workflows, elevating digital governance and ethics, and reforming traditional academic assessment. The implication is that universities must move beyond tool adoption toward curriculum-wide transformation aligned with industry, government, and social needs.